2023
DOI: 10.3390/separations10070380
|View full text |Cite
|
Sign up to set email alerts
|

Purification of High-Purity Tin via Vertical Zone Refining

Abstract: The present investigation delves into the potential of vertical zone refining as an effective purification technique for achieving high-purity tin (Sn) metal. The utilization of vertical zone refining offers distinct advantages over traditional horizontal zone refining, as it allows for enhanced control over the molten zone and solid–liquid interface, ultimately leading to superior impurity separation efficiency. The present study reveals that the solute partition coefficients (k0) of various impurity elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The distillation process has been successfully used for the production of high pure metals and percentage of purity can reach up to 5N level. [ 1,139–143 ] However, a combination of vacuum distillation and zone melting process can upgrade the purify even up to 7N. [ 140 ] Zone melting: Zone melting is a method of impurity segregation by melting.…”
Section: Potential Techniques For Materials Purificationmentioning
confidence: 99%
See 3 more Smart Citations
“…The distillation process has been successfully used for the production of high pure metals and percentage of purity can reach up to 5N level. [ 1,139–143 ] However, a combination of vacuum distillation and zone melting process can upgrade the purify even up to 7N. [ 140 ] Zone melting: Zone melting is a method of impurity segregation by melting.…”
Section: Potential Techniques For Materials Purificationmentioning
confidence: 99%
“…[ 17–21 ] This process is used to ultra‐purify many metals and materials. [ 11,23,139,144–146 ] It is the most efficient purification method as it can purify materials even up to 13N, without any other associate refining technique. [ 146 ] Purification efficiency can be improved by optimizing the molten zone length, zone travel rate, and stirring of the zone. Czochralski method: This is a very useful technique to grow bulk single crystals of materials having large diameters.…”
Section: Potential Techniques For Materials Purificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-transition metal cations, including Pb 2+ , Sn 2+ , Bi 3+ , and Sb 3+ , have a wide variety of applications in electrochemical energy storage [1,2] high-temperature superconductivity [3][4][5], catalysis [5][6][7], gas sensors [8][9][10], birefringent material [11][12][13][14], nonlinear optical crystals [15][16][17][18], etc. By analyzing many existing studies, it was found that the introduction of post-transition metal cations containing stereochemically active lone-pair electrons is a good strategy to enhance optical properties.…”
Section: Introductionmentioning
confidence: 99%